Poverty alleviation through NGO interventions: A case study of Balochistan - Baloch, Dr. Mumtaz A. (Hanken, 2015)
Balochistan is the most resourceful province of Pakistan but it is the poorest in terms of the human development indicators. The Balochistan Rural Support Programme (BRSP), an autonomous non-profit organization aiming to improve the livelihoods of the rural poor in Balochistan, is one of the ten RSPs in Pakistan. This study evaluated the impacts of BRSP interventions and found that almost all of the BRSP’s member households are surviving below the poverty line. However, BRSP has contributed in increasing agricultural production and improving household incomes but at very small-scale.